FOXO transcription factors - a potential therapeutic target in civilization diseases. - Agnieszka Przezak; Tomasz Sroczyński; Weronika Bielka (Polish Pharmaceutical Society, 2021)
Forkhead box O family member proteins (FOXOs) are nuclear transcription factors which mediate the inhibitory action of insulin or insulin-like growth factor (IGF-1) on key functions in cells. They are expressed in nearly all tissues and they participate in controlling a large amount of processes occurring in cells such as proliferation and differentiation of cells, cell cycle progression, apoptosis, or reparation of deoxyribonucleic acid. Furthermore, they are involved not only in oxidative stress response or redox signaling, but also in glucose and lipids metabolism. They are generally responsible for maintaining the cellular homeostasis in response to changes in internal and external environment. The group of described molecules consists of four protein members called FOXO1 (FKHR), FOXO3A (FKHRL1), FOXO4 (AFX1) and FOXO6. The impaired activity of FOXO proteins is associated with development of metabolic syndrome and civilization diseases, including diabetes mellitus, its complications (diabetic nephropathy, retinopathy, diabetes-related muscle atrophy, cardiovascular diseases, impaired fracture and wound healing) and different types of cancers (prostate cancer, gliomas, thymic lymphomas, angiomas). There are two groups of synthesized chemical molecules that affect activity of FOXO1 and may be useful for treating for metabolic diseases, such as inhibitors of FOXO1 or modulators of signaling pathway of the gene FOXO1. Substances naturally occurring in the environment (for instance curcumin or magnoflorine) show similar properties and abilities to modulate action of all kind of FOXO proteins. In our article we describe, the role of FOXO transcription factors in a state of health and disease, especially in civilization diseases. Moreover, we briefly present already synthesized pharmaceutical drugs and natural substances which may affect the activity of these proteins, as well as we point at potential targets for future interventions in civilization diseases based on modifications of proteins FOXO activity or their genes.